Bringing Education Back Home: Rethinking the Charter School Expansion in Nashville Public Schools - William M. Gabelman (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
The purpose of this research is to examine the extensive expansion of charter schools in the Metropolitan Nashville Area and best project whether the Metro Nashville Public School Board’s charter school policies are the best option for Nashville students, teachers, and taxpayers. This paper analyzes existing research on charter schools, particularly in regions most easily comparable to Nashville, TN and compares the research to the current state of the Nashville public schools system. The data suggest that, while a limited number of small charter schools can enhance student performance, the more charter programs expand into Nashville, the less effective they are.